Relationship between internal and external training load in field hockey - Tuft, K.; Kavaliauskas, M. (International Journal of Strength and Conditioning, 2021)
Training load monitoring in team sports is important in order to plan and evaluate training strategies and ensure optimal performance. Integration of internal and external training load measures into a single training efficiency metric reduces the effect of confounding variables on training loads. The purpose of this study was to generate a training efficiency metric to evaluate in-season field hockey training. Further, the relationship between players' perceived wellness the training efficiency metric was determined. Internal (training impulse and session rating of perceived exertion; TRIMP and sRPE) and external (total distance, high-speed distance, acceleration load, high-power distance, metabolic work, mechanical work, and impulse) training load was collected over a 6-week period for 11 male national level field hockey players (21.1 ± 1.2 years, 178.7 ± 8.6 cm, 4.6 ± 6.3 kg). The relationships between internal and external training load were assessed, and two training efficiency models were generated through mixed model analyses using sRPE and TRIMP. Subsequently, the relationships between training efficiency and perceived wellness were examined. The statistical analyses determined that total distance, high-speed distance, high-power distance, and metabolic work (r = 0.311-0.573) were included in the TRIMP training efficiency model. The sRPE training efficiency model included total distance, high-speed distance, high-power distance, metabolic work, and mechanical work (r = 0.329-0.757). Moreover, neither of the training efficiency models were related to daily cumulative wellness scores (TRIMP: r = -0.046; p = 0.336; sRPE: r = -0.034; p = 0.370). The study showed that the sRPE training efficiency model provided a better reflection of in-season field hockey training demands than the TRIMP model. Additionally, practitioners are not advised to adjust training based on acute changes in players' perceived wellness.